The Impact of Anti-Diabetics on Platelets Function and Cardiovascular Outcomes in Type 2 Diabetes Mellitus: A Narrative Review - Muthanna Zaki; Mohammed Abed; Fawaz Alassaf (Al-Anbar Medical Journal)
Increased atherosclerosis is a major risk factor for atherothrombotic disorders in patients with type 2 diabetes mellitus (T2DM). Changes in platelet metabolism and alterations in intra platelet signaling pathways are the main contributors to the pathogenesis of atherothrombotic complications of diabetes. In addition, advances in understanding the action of some anti-diabetics have demonstrated probable effects of these agents on platelet function and thrombotic state in T2DM. This review aimed to explore the possible mechanistic association between anti-diabetic agents and the development of thromboembolic disorders, considering the effect of drugs on platelet function and their impact on cardiovascular outcomes in diabetic patients. The cochran Library, PubMed, and Google Scholar were searched to analyze related publications. The relationship between anti-diabetic medications and the alterations in platelets function, in addition to the impact of the drugs on the occurrence of thromboembolic disorders in diabetic patients and their relation to cardiovascular events, were the main targets. Ninety-three published articles from November 1999 until February 2024 met the requirements for inclusion in this review. We realized various mechanisms responsible for enhanced platelet aggregation in T2DM, represented by immature, large, or activated platelets in the altered metabolic environment, against the background of vascular damage in DM. In parallel, analyzing the impact of anti-diabetics on platelet aggregation revealed that most of them are believed to have favorable protective effects against thrombotic disorders via reducing platelet activation and aggregation. Conversely, some anti-diabetics may exhibit negative consequences by exacerbating platelet hyperactivity and possibly predisposing to a higher incidence of thrombotic events in diabetic patients. When prescribing anti-diabetic agents to patients with T2DM, especially those at high risk of developing cardiovascular problems, we should consider these outcomes with proper monitoring of coagulation status.